Strategi Nelayan Buruh Bertahan Hidup di Musim Paceklik Di Perairan Teluk Tomini Kabupaten Bonebolango Gorontalo - Syamsuddin, Syamsuddin (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2024)
This study is about the survival of fishermen whose lives depend directly on marine products with seasonal natural conditions making fishermen very dependent on seasonal natural conditions caused by unpredictable weather. This study was conducted in May to July 2020. The approach used in this study was qualitative with a descriptive research type, with 15 informants taken by Purposive Random Sampling. Data collection techniques used include observation, interviews, and document studies. The data analysis technique used is the Miles and Huberman model, namely data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the study, there are several survival strategies for fishermen during the lean season, namely: looking for side jobs, either as farm laborers, housekeepers, motorcycle taxis and others; taking loans from formal or non-formal institutions; involving family members assisted by wives, children and younger siblings; using savings that have been saved in the form of money and gold, and utilizing assistance received from the government.